Studi perencanaan pelabuhan Glagah di Pantai Selatan Daerah Istimewa Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
The Yogyakarta Provincial Fisheries Service identified Glagah Coast as one of the most suitable site for a future development of fishing port. It is well located with regard'to the potency of marine fish resource, well supported by acces road and hinterland, area avaibility and other supporting facilities. The natural constraint is that the coast is exposed to heavy swell from Indonesian Ocean. Therefore the port has to be protected by breakwater, which is a very high cost structure. The design of the port is based on the number and size of ships to be accomodated and the site physical conditions such as bathimetry map, variation of water level due to astronomical tide, waves approaching the coast from various direction, and movement of sand along the coast. The tide ranges from 1,2 m to the maximum of about 2,15 m